Fermentation Effectiveness Of Various Ratios Of Palm Oil Mill Effluent (Pome) And Empty Fruit Bunch (Efb) Mixture By Lysinibacillus Sp. For Solid Biomass Fuel Production - Dominic, Debbie Anak (2024)
Biovalorization of agro-industrial wastes to produce an alternative energy source such as solid biomass fuel is gaining attention worldwide due to its potential to produce sustainable valuable products. In the current study, the potential use of palm oil mill effluent (POME) waste and empty fruit bunches (EFB) was explored for the production of solid biomass fuel. Fermentation of POME and EFB was carried out in a benchtop bioreactor at 37 ± 2 °C, 180 rpm for five-days in the presence of Lysinibacillus sp. bacteria, followed by oven drying. Two main categories of fermentation media consisted of autoclaved and non-autoclaved mixture of POME and EFB are explored to investigate the metabolic activities of Lysinibacillus sp. Additionally, the different composition ratio of POME and EFB mixture of the fermentation media is elucidated to assess the ideal fermentation conditions, particularly their impact on CEV for solid biomass fuel production. Among the tested conditions, Group 4 exhibited the highest calorific energy value (CEV) of 29.54 MJ/kg after fermentation at day 1. Fermentation in the presence of Lysinibacillus sp. showed efficient removal of biochemical oxygen demand (BOD) at 27.64 ± 0.53 %, chemical oxygen demand (COD) at 70.42 ± 0.01 %, oil and grease at 87.68 ± 0.14 %, and total suspended solids (TSS) 93.94 ± 2.03 %. The concentration of ammoniacal nitrogen (NH3-N) remained unchanged before and after fermentation in all conditions.